DEVELOPMENT OF INTERACTIVE SCIENCE LEARNING E-MODULES BASED ON PROJECT BASED LEARNING TO IMPROVE SCIENCE PROCESS SKILLS AT ISLAMIC ELEMENTARY SCHOOL - Elma Yuniarti; Sutiah Sutiah; Rini Nafsiati Astuti (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2024)
Interactive Science Learning E-Module teaching materials are developed with science process skills. The interactive science learning e-module has the form of software that can be used with the help of a laptop, computer and cellphone. Interactive e-Modules are presented in PDF form, making them easier for educators and students to use, and can be used offline, but there are several menus such as quizzes, learning videos and evaluations that cannot be accessed if you are not connected to the internet. This research is Research and Development (R&D), by applying five ADDIE model stages (analyze, design, develop, implement, and evaluate). Stage analyze includes analysis of educators and students.  The design stage includes preparing the e-module outline in the form of selecting media and e-module formats as well as designing the learning content in the e-module. The development stage includes the development of data collection instruments. The data collection instruments in this research are eligibility sheets for validators and science learning practitioners, as well as pretest and posttest questions for science process skills. This instrument was developed based on review by supervisors, assessments by validator lecturers, science teacher learning practitioners, and trials on students. The implementation stage includes the application of the e-module that has been developed for class IV students at MI Tarbiyatussibyan Banyuwangi. The experimental design used at this stage is one group pretest-posttest. The evaluation stage includes the form of evaluation carried out at each ADDIE stage. The data analysis technique used is the normality test and t test.The research results show that the interactive science learning e-module based on project based learning that was developed is very effective and interesting to use in science learning. The science e-module is effective in improving science process skills because the results of field trials show students' enthusiasm in learning science and students who easily understand science material with the stages of science process skills. Science process skills can also provide innovation to educators in creating enjoyable science learning.